(untitled) (Medico Legal Update, 2020)
Background: Adolescence is a transitional period from childhood to adulthood characterized by significant physiological, psychological and social changes. World Health Organization defines Teenage Pregnancy as “any pregnancy from a girl who is 10-19 years of age”, the age being defined as her age at the time the baby is born. Aim of the Study: To study the correlation study between of fetal risk and adolescent pregnancy. Patients and Method: A cross sectional study conducted in Department of Obstetrics and Gynecology in Salah El-Din teaching hospital at the period from the 1st of Feb. 2018 to the end of August 2018. Convenient sample of (100) teenage pregnant women, who are willing to participate in this study and available at the time of data collection include. Results: The frequent outcome of pregnant women was birth (32%), followed by; birth & oligohydrominous (14%), the neonatal complications were present in 68% of pregnant woman’s neonates. The delivery complications were absent in 32% of pregnant women while present as episiotomy (50%), in general, delivery complications were present in 68% of pregnant women. Conclusion: The neonatal complications were present in 68% of pregnant women.